Strain-tunable electronic, optical and thermoelectric properties of two-dimensional Janus SbXI (X=S, Se, Te) monolayers: A first-principles study - Gonzalo, Fredy Mamani; Rivera, Victor José Ramirez; Sambrano, Julio R. [UNESP]; Piotrowski, Maurício Jeomar; Flores, Efracio Mamani (Elsevier, 2025)
The exploration of novel, atomically thin, and stable two-dimensional (2D) materials remains an important and active area of study, driving progress in both fundamental science and practical applications within contemporary materials research, particularly in electronic, thermoelectric, and optical domains. Through first-principles density functional theory (DFT) calculations, Three semiconducting Janus monolayers was systematically investigated: SbSI, SbSeI and SbTeI. The comprehensive analysis demonstrates excellent dynamical and energetic stability, indicating the feasibility of mechanical exfoliation for experimental realization. Electronic structure calculations reveal indirect bandgaps of 1.57 (2.12), 1.30 (1.80), and 1.22 (1.64) eV for SbSI, SbSeI, and SbTeI, respectively, using PBE (HSE06) functionals, with the SbSeI monolayer exhibiting an exceptional electron mobility of 213.96 cm 2 V−1s−1, surpassing that of the well-established MoS 2 . Remarkably, at 800 K, the SbSeI monolayer achieves outstanding thermoelectric performance, characterized by a figure of merit ( Z T ) of 5.39, facilitated by an ultralow lattice thermal conductivity of 0.14 W/mK. Furthermore, upon application of +8% biaxial strain, the SbTeI monolayer displays notable optical properties, including a high reflectivity of 64.00% in the ultraviolet region ( ∼ 250 nm) and an absorption coefficient of 121.98 × 10 4 cm−1. These findings underscore the significant potential of Janus SbXI (X = S, Se, Te) monolayers for next-generation energy conversion applications, offering promising avenues for efficient energy harvesting and thermal management while enabling novel functionalities in nanoscale optical devices.